2017
DOI: 10.1161/jaha.116.004512
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Untimely Implantable Cardioverter/Defibrillator Implantation by Intensified Heart Failure Therapy Optimization Supported by the Wearable Cardioverter/Defibrillator—The PROLONG Study

Abstract: BackgroundOptimal timing of implantation of an implantable cardioverter/defibrillator (ICD) after newly diagnosed heart failure is unclear given that late reverse remodelling may occur. We aimed to analyze left ventricular ejection fraction (LVEF) after diagnosis of an LVEF ≤35% during optimization of heart failure drug therapy.Methods and ResultsOne hundred fifty‐six patients with newly diagnosed LVEF ≤35% receiving a wearable cardioverter/defibrillator (WCD) were analyzed. WCD was prescribed for 3 months unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 32 publications
7
81
0
4
Order By: Relevance
“…A structured approach for prolonged but, however, secured optimization of heart failure therapies has been recently published [17]. …”
Section: Discussionmentioning
confidence: 99%
“…A structured approach for prolonged but, however, secured optimization of heart failure therapies has been recently published [17]. …”
Section: Discussionmentioning
confidence: 99%
“…DANISH underlines that it is important to establish optimal HF medication before decision for permanent ICD implantation is taken. Optimization of HF medication and reverse ventricular remodeling takes time, which can be securely provided by the WCD as presented in the PROLONG study …”
Section: Discussionmentioning
confidence: 99%
“…The PROLONG study included patients being prescribed with a WCD at Hannover Medical School between June 2012 and January 2016. The detailed study protocol and results have been published elsewhere . The study complies with the Declaration of Helsinki and was approved by the local ethics committee.…”
Section: Introductionmentioning
confidence: 99%
“…As LVEF improves, the need for an ICD for primary prevention of SCD decreases. A study by Duncker et al also showed similar results, with approximately 1/3rd of the patients who received ICDs experiencing LVEF improvement beyond the currently recommended 90 day waiting period …”
Section: Discussionmentioning
confidence: 67%